PENINGKATAN PEMAHAMAN KONSEP SAINS DI MADRASAH IBTIDAIYAH MELALUI PERBAIKAN BAHAN AJAR - Wibowo, Agus Mukti (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2012)
Understanding is very important in science learning, especially at the level of Madrasah Ibtidaiyah. Students’ concepts understanding tend to similarity to the explanations and examples provided by the teacher or teaching materials. In fact, most teaching materials and textbooks are not reviewer both in terms of content and material. Corrected and modified teaching material to be improved students’ understanding.